Climate Change Vulnerability Analysis of Baluran National Park - Beny Harjadi (Universitas Muhammadiyah Surakarta, 2016)
Every ecosystem has a different level of susceptibility to environmental disturbances it receives, both from natural factors or anthropogenic disturbance. National Park (NP) Baluran is one national park that has a representation of a complete ecosystem that includes upland forest ecosystems, lowland forests, coastal forests, mangroves, savanna and evergreen forest. The objective of this study is to get a formula calculation of vulnerability analysis of constant and dynamic factors. Baluran NP vulnerability assessment to climate change done by looking at the dynamic and fixed factors. Vulnerability remains a vulnerability factor to the condition of the original (control), whereas vulnerability is the vulnerability of the dynamic change factors which affected the condition from the outside. Constant Vulnerability (CV) in Baluran NP dominated resistant conditions (61%), meaning that the geomorphology and other fixed factors (slope and slope direction/aspect, then the condition in Baluran NP sufficiently resilient to climate change. Dynamic Vulnerability (DV) is the vulnerability of an area or areas that change because of pressure from external factors. DV is influenced by climatic factors (WI = Wetness Index), soil (SBI = Soil Brightness Index), and vegetation (GI = Greenness Index). DV in Baluran NP from 1999 to 2010 shifted from the original category of being (84.76%) and shifted to the susceptible (59.88%). The role of remote sensing for the analysis of raster digital system, while the geographic information system to display the results of cartographic maps.